An Improved Method of Theabrownins Extraction and Detection in Six Major Types of Tea (Camellia sinensis). (27th September 2022) - Lee, Tzan-Chain; Zang, Qian-Nan; Lin, Kuan-Hung; Hu, Hua-Lian; Lu, Ping-Yuan; Zhang, Jing-Yao; Kang, Chun-Qin; Li, Yan-Jie; Ko, Tzu-Hsing
Abstract : Tea pigments consisting of theabrownins (TBs), theaflavins (TFs), and thearubigins (TRs) affect the color and taste of tea. TBs include a variety of water-soluble compounds, but do not dissolve in n-butanol and ethyl acetate. Previously, the traditional method of TB extraction only mixed tea with n-butanol, and TBs were retained in the water phase. However, without ethyl acetate extraction, TFs and TRs remained in the water phase and affected the detection of TB content. Although an improved method had been devised by adding an ethyl acetate extraction step between tea production and n-butanol extraction, the proportional equation for calculating TB content (%) was not yet developed. In this study, we compared the absorbance at 380 nm ( A 380 ) of TB solutions from six major types of tea (green, yellow, oolong, white, black, and dark teas) extracted by improved and traditional methods from the same tea samples. Significantly lower A 380 values were obtained from TB solutions via the improved method compared to the traditional method for six major types of tea, and the highest and lowest slops in TB concentrations from A 380 analyses were from dark tea and green tea, respectively. Moreover, newly developed equations for TB content in those six tea types extracted by the improved methods were also established.